2003
DOI: 10.1161/01.cir.0000062702.60708.c4
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL Promotes the Survival and Proliferation of Primary Human Vascular Endothelial Cells by Activating the Akt and ERK Pathways

Abstract: Background-TRAIL protein is expressed in the medial smooth cell layer of aorta and pulmonary artery, whereas endothelial cells express all TRAIL receptors (TRAIL-Rs). Methods and Results-The role of TRAIL/TRAIL-Rs in vascular biology was investigated in primary human umbilical vein endothelial cells (HUVECs) and aortic endothelial cells, which showed comparable surface expression of death (TRAIL-R1 and -R2) and decoy (TRAIL-R3 and -R4) TRAIL-Rs. TRAIL activated the protein kinase Akt in HUVECs, as assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
282
3
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(309 citation statements)
references
References 24 publications
18
282
3
3
Order By: Relevance
“…Several investigators [25,44] have shown that ERK activity can act as a survival signal in endothelial apoptosis, and we recently observed that inhibition of ERK potentiated TNFinduced endothelial apoptosis [12]. However, in the present experiments, inhibition of the MEK-ERK pathway in EC WT decreased doxorubicin-induced caspase-3 activity by 73% and also curbed the cytotoxicity of the drug by 49%, and the corresponding values for EC DNp38 were 56% and 58%, respectively (Fig.…”
Section: Participation Of Other Map Kinases and Akt In Doxorubicin-incontrasting
confidence: 48%
See 1 more Smart Citation
“…Several investigators [25,44] have shown that ERK activity can act as a survival signal in endothelial apoptosis, and we recently observed that inhibition of ERK potentiated TNFinduced endothelial apoptosis [12]. However, in the present experiments, inhibition of the MEK-ERK pathway in EC WT decreased doxorubicin-induced caspase-3 activity by 73% and also curbed the cytotoxicity of the drug by 49%, and the corresponding values for EC DNp38 were 56% and 58%, respectively (Fig.…”
Section: Participation Of Other Map Kinases and Akt In Doxorubicin-incontrasting
confidence: 48%
“…Activated Akt regulates survival by phosphorylating numerous cellular proteins, such as caspase-9 [20], Bad [21], the forkhead family of transcription factors [22], GSK-3β [23], and NF-κB [24]. PI3-K/Akt mediates survival in a variety of cell types, including endothelial cells [16,25], and there is evidence that sustained activation of Akt suppresses doxorubicin-induced apoptosis in gastric adenocarcinoma [26].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been demonstrated that low concentrations of TRAIL activate signal-transduction pathways related, respectively, to ERKs and Akt, the latter depending upon PI3K activation (Secchiero et al, 2003), whereas p38K is not activated. Besides, TRAIL at a concentration of 100 ng ml À1 induces apoptosis in combination with the PI3K inhibitor LY294002 in human vascular endothelial cells through activation of the extrinsic pathway, causing progressive cleavage of caspase-8 and caspase-3 with concurrent reduction of the antiapoptotic gene bcl-2 and early loss of the short form of the cellular FLIP (Alladina et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanism underlying DR5-mediated inhibition of NFkB remains unclear, these observations raise questions about the biological significance of NF-kB activation by Apo2L/TRAIL. Indeed, the physiological relevance of the observation that Apo2L/TRAIL can stimulate other intracellular kinase cascades such as the JNK, MAPK and PKB/Akt pathways has yet to be established as well (Lin et al, 2000;Secchiero et al, 2003;Zhang et al, 2003;Varfolomeev et al, 2005) (Figure 2). …”
Section: Alternative Signaling Events Regulated By Apo2l/trailmentioning
confidence: 99%